2009
DOI: 10.1002/clc.20343
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of Smoking Light Cigarettes on Coronary Microvascular Functions

Abstract: Background: To date, there has been no study comparing the possible acute effects on coronary microvascular functions of smoking light cigarettes (those with low tar and nicotine yield) and regular cigarettes. Methods: Twenty healthy volunteers (8 women and 12 men; mean age, 25.8 ± 5.8 years) were included in a single-blind, open-label, cross-over study to compare the effects of smoking light cigarettes (containing 0.6 mg nicotine, 8 mg tar, 9 mg carbon monoxide) and smoking regular cigarettes (containing 0.9 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Smoking is known to cause temporary coronary vasospasm, 12 and microvascular ischemia, 60 which may result in troponin elevation. The lack of association between smoking intensity and subclinical myocardial injury in our study could be explained by the fact that high-sensitivity troponin assays were not performed in MESA, 61 and participants were instructed to abstain from smoking on the morning of the MESA visit.…”
Section: Subclinical Myocardial Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…Smoking is known to cause temporary coronary vasospasm, 12 and microvascular ischemia, 60 which may result in troponin elevation. The lack of association between smoking intensity and subclinical myocardial injury in our study could be explained by the fact that high-sensitivity troponin assays were not performed in MESA, 61 and participants were instructed to abstain from smoking on the morning of the MESA visit.…”
Section: Subclinical Myocardial Injurymentioning
confidence: 99%
“…9 Acute exposure to cigarette smoking may be associated with inflammation, thrombosis, endothelial dysfunction, arterial stiffness, and coronary microvascular dysfunction. [10][11][12][13][14][15][16][17] Cohort studies have traditionally been used to examine the chronic effects of smoking, but have rarely been used to evaluate immediate inhalational smoking exposure. 18 Long-term exposure is commonly assessed using smoking duration (years), or cumulative exposure (pack-years).…”
Section: Introductionmentioning
confidence: 99%
“…However, neovascularization need not always be associated with pathological processes. An example of positive impact may be effects on the cardiovascular system in the case of ischemic heart disease (1)(2)(3)(4)(5).…”
mentioning
confidence: 99%
“…In a large study involving 881 patients, intracoronary Doppler ultrasound flow measurements demonstrated significantly lower acetylcholine-induced hyperaemia in smokers compared to non-smokers (50% vs. 81%) [37]. The coronary flow reserve (CFR) in the left anterior descending artery declined significantly from 2.8±0.56 to 2.31±0.51 after smoking light cigarettes (measured by nicotine and tar content in the cigarette), and, similarly, from 2.8±0.56 to 2.21±0.45 after smoking regular cigarettes [38].…”
Section: Introductionmentioning
confidence: 74%